PENDIDIKAN AGAMA ISLAM DALAM KELUARGA DAN MASYARAKAT - Hair, Moh Afiful; Subhan, Moh (Fakultas Agama Islam Universitas Islam Madura, 2018)
Education in the family is an important aspect to build a person's behavior. Usually the education in a family is condacted with the religious values and ethics, which consists of behavior, manners and use attitude used in everydays life. The aim of this writing is to discuss the role of religious education in the family and society. This method used library research with the descriptive and explorative approach. The conclusions are that the role of the Islamic education: (1) as the foundation of religious education in a family which used to form the children’ good attitude and behavior, (2) functions as tools to convince people to the almighty of God, (3) as a foundation to build the society character for the Indonesian people to improve the nation.